A Measurement Invariance Analysis of the General Self-Efficacy Scale on Two Different Cultures. (December 2014) - Teo, Timothy; Kam, Chester
The 10-item General Self-Efficacy Scale (GSES) was developed to assess an individual's beliefs to cope with a variety of situations in life. Despite the GSES being used in numerous research from researchers in different countries and presented in different languages, little is known about the use of its validity in an Asian culture. The aim of the present study is to assess the measurement invariance of the GSES across two countries with distinctly different cultures. Results revealed that although there was full metric invariance in the two samples, only partial scalar invariance was achieved as the intercepts of 4 out of 10 items were non-invariant.